EEG based human emotion recognition using discrete wavelet transform - Murugappan, M. (School of Mechatronic Engineering, Universiti Malaysia Perlis, 2010)
This thesis belongs to the framework of discrete emotion recognition research using EEG signals. More precisely, it focuses on the study of EEG signal processing and classification techniques in order to design and discrete emotion recognition system.